Allelopathy of extracts of Cyperus rotundus and Oxalis latifolia on snapdragon seeds germination - Pêgo, Rogério Gomes; Fialho, Cíntia Maria Teixeira (Ornamental Horticulture, 2018)
Snapdragon (Anthirrhinum majus L.) is an ornamental plant propagated by seeds and usually cultivated in beds. In production fields occur many weeds, such as Cyperus rotundus and Oxalis latifolia, which can decrease flower production by competition or releasing allelopathic components. However, there is few knowledge about the effect of these allelopathic components on snapdragon seed germination. Therefore, this study aimed to determine the allelopathic potential of aqueous extracts of C. rotundus and O. latifolia on the germination of snapdragon. For this, 10 g of material vegetal from whole plants of C. rotundus or O. latifolia were ground in 100 mL of water (10% w v-1). The dilutions of aqueous extracts in 75%, 50%, 25% and 0 were prepared using distilled water. The seeds were kept in paper moistened with extracts, in box gerbox-type, and conditioned in a germination chamber for 11 days. After 11 days the percentage of germination, vigor, germination speed index (GSI), percentage of abnormal seedlings and dead seeds, root length and shoot seedlings were evaluated. Extracts of C. rotundus and O. latifolia reduced the percentage of seed germination by up to 17.6% and 43.7%, respectively. The vigor was reduced from 55.0% to 28.5% and IVG reduced from 27 to 12 in extracts of O. latifolia. The maximum of 49.5% and 35.5% of dead seeds was obtained in extracts of O. latifolia and C. rotundusrespectively. The highest concentrations of extracts of both species altered the morphology of snapdragons seedlings reducing the length of radicle and shoot.